REPOSITIONING DEVELOPMENT AGENDA IN NIGERIA: THE IMPERATIVES OF ENVIRONMENTAL CLEAN-UP STRATEGIES IN THE NIGER DELTA REGION - Nnajoel, Prince; NWIEKPUGI BRIGHT PhD., PORONAKIE; GOODNEWS PhD, WABAH; B.D., GBEGEH, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
Oil and Gas extraction globally, has devastating effects on host communities environment most especially their socio-economic well-being. In Nigeria, particularly the Niger Delta Region, environmental degradation through decades of intensive oil and gas development have acquired international attention and new organizational arrangements for the implementation of the UNEP’S Report (2011) to ensure environmental quality, human welfare and social justice. In some cases, environmental devastations have attained genocidal proportions such that people’s means of livelihoods and fundamental life support systems-air, water and food or agricultural resources are near extinction. The region exhibits a high degree of resource alienation due to her strategic economic location and high resource advantages. The acquisition of large expanse of land for industrial location, building of refineries, fertilizer companies etc, besides impacting the environment negatively have also ensured massive decline in agricultural out-put, out-migration of able-bodied youths, over exploitation of the fast disappearing natural resources, engendered social rifts and intensified conflicts. This paper thus highlights the imperatives of environmental clean-up strategies to the recovery and sustainability of the Niger Delta. This is because sustainable environmental development is a precondition for the sustainable economic development of the region. Hence, the authors affirmed that failure to urgently address the challenges of poverty, unemployment and the continued neglect of infrastructural development in the region from which Nigeria’s wealth derives; can only breed the ogre of criminality, social unrest, demand for resource control/autonomy and renewed ethnic militancy among the jobless youths of the region.